Lawnmageddon - Tobin, Paul, 1965-; Chan, Ron; Rainwater, Matthew J.; Dutro, Steve (Milwaukie, OR : Dark Horse Books, 2013)
"Young adventurers Patrice Blazing and Nate Timely fend off a 'fun-dead' neighborhood invasion in Plants vs. Zombies: Lawnmageddon!"--From publisher's web site.
Based on the video game Plants vs. Zombies.
"This volume collects Plants vs. zombies: Lawnmageddon #1--#6, originally serialized by Dark Horse Digital."
Keywords: Plants vs. zombies (Game) -- Comic books, strips, etc; Plants vs. zombies (Game) -- Juvenile fiction; Zombies -- Comic books, strips, etc; Zombies -- Juvenile fiction; Plants -- Comic books, strips, etc; Plants -- Juvenile fiction; Video games -- Comic books, strips, etc; Video games -- Juvenile fiction; Action and adventure comics; Adventure fiction (Juvenile); Cartoons and comics; Graphic novels (Juvenile)